Refugees’ Access to Housing and Residency in German Cities: Internal Border Regimes and Their Local Variations - El-Kayed, Nihad (2018)
This article examines how state regulations, market barriers, racist discrimination as well as NGOs interact and create internal border regimes by enabling, as well as restricting, access to social and civil rights connected to housing and the freedom of movement and settlement for refugees. Our contribution builds on an analysis of federal and state regulations on housing for refugees who are either in the process of seeking asylum or have completed the process and have been granted an asylum status in Germany. The analysis aims to dissect the workings of these regulations in order to develop a detailed understanding of how these internal border regimes define barriers and access to social and civil rights. In addition to legal and regulatory barriers at the federal, state, and local levels, we identify several other barriers that affect if, how, and when refugees are able to enter local housing markets. We will examine these barriers based on an exemplary analysis of the situation in the cities of Berlin and Dresden, whereby we will apply concepts from border as well as citizenship studies to obtain a deeper understanding of the processes at hand. While contributions to the realm of border studies have so far mostly concentrated on national or EU borders, our approach follows recent literature that emphasises the need to analyse the workings of borders internal to nation-states but has so far not addressed local variations of the ways in which refugees are able to access their right to housing. In taking up this approach, we also stress the need to look at local dimensions of an increasing civic stratification of refugee rights, which past research has also conceptualised primarily on the national level. In both cities, we have collected administrative documents and conducted interviews with refugees, NGOs, and representatives from the local administration. Based on this material, we analyse the workings of administrative barriers at the state and local levels along with market barriers and discriminatory practices employed by landlords and housing companies at the local level. In most cases, these conditions restrict refugees’ access to housing. We will contrast these obstacles with insight into the strategies pursued by refugees and volunteers in their efforts to find a place to live in the city.